Awake, sedated or anaesthetised for regional anaesthesia block placements?: A retrospective registry analysis of acute complications and patient satisfaction in adults. Issue 10 (October 2016) - Kubulus, Christine; Schmitt, Kathrin; Albert, Noemi; Raddatz, Alexander; Gräber, Stefan; Kessler, Paul; Steinfeldt, Thorsten; Standl, Thomas; Gottschalk, André; Meissner, Winfried; Wirtz, Stefan P.; Birnbaum, Jürgen; et al.
Abstract : BACKGROUND: Whether adults should be awake, sedated or anaesthetised during establishment of regional anaesthesia is still debated and there is little information on the relative safety of each. In paediatric practice, there is often little choice but to use sedation or anaesthesia as otherwise the procedures would be too distressing and patient movement would be hazardous. OBJECTIVE(S): The objective of this study was to evaluate complications related to central and peripheral regional block and patient satisfaction in awake, sedated and anaesthetised adult patients. DESIGN: A retrospective registry analysis. SETTING: The German Network of Regional Anaesthesia database was analysed between 2007 and 2012. PATIENTS: We included data of 42 654 patients and defined three groups: group I awake ( n = 25 004), group II sedated ( n = 15 121) and group III anaesthetised ( n = 2529) for block placement. MAIN OUTCOME MEASURES: Odds ratios [OR; 95% confidence interval (CI)] were calculated with logistic regression analysis and adjusted for relevant confounders to determine the risk of block-related complications in sedated or anaesthetised patients compared with awake patients. RESULTS: Rates of local anaesthetic systemic toxicity were comparable between the groups [awake 0.02% (95% CI: 0.002 to 0.0375), sedated 0.02% (0.003 to 0.042) and anaesthetised 0% (0 to 0.12%)], as were the rates of pneumothorax [awake 0.035% (0 to 0.074), sedated 0% (0 to 0.002) and anaesthetised 0.2% (0 to 0.56)]. Considering peripheral nerve blocks, sedated patients had a decreased risk for multiple skin puncture [adjusted OR: 0.78 (95% CI: 0.71 to 0.85), premature termination [0.45 (0.22 to 0.91)], primary failure [0.58 (0.40 to 0.83)] and postoperative paraesthesia [0.35 (0.28 to 0.45)], but an increased risk for a bloody tap [1.82 (1.50 to 2.21)]. General anaesthesia increased the risk of a bloody tap [adjusted OR: 1.33 (95% CI: 1.01 to 1.78)] and multiple skin puncture [1.28 (1.12 to 1.46)], but decreased the risk for postoperative paraesthesia [0.16 (0.06 to 0.38)]. In neuraxial sites, sedation increased the risk for multiple skin puncture [adjusted OR: 1.18 (95% CI: 1.09 to 1.29)], whereas block placement under general anaesthesia decreased the risk for multiple skin puncture [0.53 (0.39 to 0.72)] and bloody tap but significantly increased the risk for postoperative paraesthesia related to a catheter [2.45 (1.19 to 5.02)]. Sedation was associated with a significant improvement in patient satisfaction. CONCLUSION: Sedation may improve safety and success of peripheral nerve block placement. Block placement under general anaesthesia in adults should be reserved for experienced anaesthesiologists and special situations.